1990
DOI: 10.21273/hortsci.25.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fall Ethephon Applications on Bloom Delay, Flowering, and Fruiting of Peach and Prune

Abstract: Studies in the use of fall ethephon to delay bloom in peach and prune were carried out during 1985-87. In `Italian' prune, ethephon at 250 and 500 mg·liter-l at 10% leaf-drop stage delayed bloom 13 and 16 days, respectively. Only a 5- and 7-day bloom delay occurred when applied at 50% leaf-drop stage. Fruit set and yield were not reduced in `Italian' prune when ethephon was applied at the 50% leaf-drop stage. Early applications, from vegetative maturity to the 10% leaf-drop stage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Although the most effective means of achieving this aim would undoubtedly be the breeding of a late ripening cultivar with improved fruit storage potential, there is also the possibility of manipulating the ripening of existing cultivars by use of growth regulators and various cultivation techniques that will delay flowering and fruit set in the orchard (Crisosto et at., 1990), or that will retard fruit development (Facteau et al, 1985;EI-Othmani et at., 1990).…”
mentioning
confidence: 99%
“…Although the most effective means of achieving this aim would undoubtedly be the breeding of a late ripening cultivar with improved fruit storage potential, there is also the possibility of manipulating the ripening of existing cultivars by use of growth regulators and various cultivation techniques that will delay flowering and fruit set in the orchard (Crisosto et at., 1990), or that will retard fruit development (Facteau et al, 1985;EI-Othmani et at., 1990).…”
mentioning
confidence: 99%
“…The benefit of bloom delay is often decreased by side effects, such as gummosis, floral abscission, or failure of floral buds to open (Coston et al, 1985;Dennis, 1976;Proebsting and Mills, 1973). Crisosto et al (1990) reported bloom delay but decreased yield in peaches [Prunus persica (L.) Batsch.]. Bloom was also delayed when ethephon was applied to 'Italian' prune (Crisosto et al, 1990).…”
mentioning
confidence: 99%
“…Crisosto et al (1990) reported bloom delay but decreased yield in peaches [Prunus persica (L.) Batsch.]. Bloom was also delayed when ethephon was applied to 'Italian' prune (Crisosto et al, 1990). However, a significant increase in yield was observed in 1 year of trials.…”
mentioning
confidence: 99%
“…In general, early application with higher concentration is more effective. For example, when applied at 10% leaf drop, 250 and 500 ppm ethephon delayed bloom in plums (Prunus domestica) by 13 and 16 days, respectively; whereas only 5 and 7 days bloom delay was observed when ethephon was applied at 50% leaf drop stage (Crisosto et al, 1990). The effectiveness of ethephon appears to be limited to the pre-dormancy stage, as serious flower bud abscission was induced when application was made after the satisfaction of CR (Durner and Gianfagna, 1991), and little or no effect was found when ethephon was applied in apricot during the dormancy stage (Grijalva-Contreras et al, 2011).…”
Section: Ethylene As a Bloom-delaying Agentmentioning
confidence: 99%